Integration of Religious Moderation in The Arabic Textbook “Mumtaz 1” at UIN Imam Bonjol Padang - Zaimatuz Zakiyah; Rezkya Afril (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2025)
Religious moderation has become a key pedagogical mandate in Indonesia’s Islamic higher education, including at UIN Imam Bonjol Padang, where Arabic instruction is expected to promote balance, tolerance, and peaceful engagement. This study examines how far the Mumtaz 1 textbook used in several undergraduate programs embeds moderation values and supports their pedagogical application. The study aims to: (1) identify moderation values across the book’s lexical, textual, visual, and task components; (2) analyze their representation using a rubric based on moderation indicators; and (3) assess the textbook’s pedagogical adequacy for fostering critical reflection and dialogic competence. Using qualitative content analysis, data were drawn from the textbook and relevant literature, then analyzed thematically according to the Ministry of Religious Affairs’ moderation framework. The findings show that moderation values appear implicitly through polite expressions, cooperative dialogues, balanced-lifestyle messages, and peaceful community depictions, but their presentation is unsystematic and provides limited support for higher-order thinking skills. The study concludes that while Mumtaz 1 contains basic elements of moderation, its effectiveness relies heavily on teacher mediation and supplementary reflective activities.